Oleoylethanolamide Modulates BDNF-ERK Signaling and Neurogenesis in the Hippocampi of Rats Exposed to Δ9-THC and Ethanol Binge Drinking During Adolescence - Silva-Peña, Daniel; Rivera, Patricia; Alén, Francisco; Vargas, Antonio; Rubio, Leticia; García-Marchena, Nuria; Pavón, Francisco Javier; Serrano, Antonia; Rodríguez de Fonseca, Fernando; Suárez, Juan (Frontiers in Molecular Neuroscience, 2019)
Oleoylethanolamide (OEA) is an endogenous N-acylethanolamide that modulates ethanol-seeking behavior and ethanol-induced neuroinflammation. In the present study we further analyze the role of OEA in hippocampal neurogenesis, BDNF-ERK signaling and spatial memory that are affected by alcohol. Additionally, we addressed the effects of OEA on the association of alcohol and cannabis, a frequent combination in human alcohol addicts, and whose long-term effects are far from being understood. To this end, OEA (10 mg/kg/day, i.p.) was pharmacologically administered for 5 days/week in a preclinical model of adolescent rats with binge-like consumption (1 day/week) of ethanol (3 g/kg, i.g.) combined or not with acute administrations of Δ9-THC (5 mg/kg, i.p.) for 5 weeks. OEA restored ethanol/THC-related decreases in both short-term spatial memory (spontaneous alternation by Y-maze) and circulating levels of brain-derived neurotrophic factor (BDNF), reduced cell proliferation (Mki67 and IdU+ cells) and maturation (Dcx, Calb1), and improved cell survival (Casp3 and BrdU+ cells) in the dorsal hippocampus. Interestingly, OEA alone or combined with THC also decreased the mRNA levels of neurotrophic factors (Bdnf, Ntf3) and the NT3 receptor TrkC, but increased the BDNF receptor TrkB in the hippocampus of ethanol-exposed rats. These effects were likely associated with a OEA-specific phosphorylation of AKT and ERK1, key signaling regulators of cell proliferation and survival. These results suggest a regulatory role of OEA in short-term spatial memory and hippocampal neurogenesis through BDNF/AKT/ERK1 signaling in response to acute THC in an alcoholic context during adolescence.